The effectiveness of dalethyne dressings for reducing bacteria in diabetic foot ulcers - Jais Suriadi; Priyono Djoko (Sciendo, 2021)
This study evaluates the effectiveness of a dalethyne dressing for decreasing bacteria in diabetic patients with infected foot ulcers.